Subcutaneous tumor volume measurement in the awake, manually restrained mouse using MRI. - Kersemans, V; Cornelissen, B; Allen, P; Beech, J; Smart, S (Wiley, 2013)
PURPOSE: To describe a combination of techniques using the excellent volumetric capacities of magnetic resonance imaging (MRI) while avoiding anesthesia and maintaining high-throughput capability for tumor volume measurement in the awake mouse. This approach presents an alternative to calipers which, although cheap, fast, and easy to use, introduce many biases for tumor volume estimation. MATERIALS AND METHODS: The murine CaNT subcutaneous xenograft model was used. A quiet and modestly T2-weighted spin-echo scan was acquired at 4.7T (TE = 15 msec, TR = 1100 msec, 0.5 mm isotropic resolution) while the awake mouse was held by hand in the magnet. This method was compared to standard MR in the anesthetized mouse and caliper measurements. RESULTS: The combination of techniques used allows rapid, accurate, and reproducible measurement of subcutaneous tumor volumes in awake mice. It is less sensitive to both intra- and interoperator-derived biases and avoids confounds from the compliance of the fat and skin around the tumor, as well as from the tumor itself. Moreover, the data remain available for retrieval and scrutiny and reanalysis. CONCLUSION: Rapid, accurate, and precise tumor volumetry can be performed in the awake mouse by handheld positioned MR.